ANALISIS KERENTANAN SOSIAL EKONOMI PETANI JERUK DI KECAMATAN SULIKI KABUPATEN LIMA PULUH KOTA - Mona Lisa (JURNAL BUANA, 2022)
This study analyzes the socio-economic vulnerability of citrus farmers in Suliki District, Lima Puluh Kota Regency. This type of research is descriptive quantitative with a population of 1697 farmers who have citrus plantations. Determination of the sample using proportional random sampling technique. The results of the study: (1) the level of social vulnerability of citrus farmers in Suliki District, Lima Puluh Kota Regency is included in the moderately vulnerable category (score 2.6-3.4) in Nagari Kurai, Suliki and Sungai Rimbang which is influenced by customary law and institutional parameters, while Nagari Tanjuang Bungo's level of vulnerability is slightly vulnerable (score 1.7-2.5) influenced by customary law and institutional parameters. (2) the level of economic vulnerability in Suliki District, Lima Puluh Kota Regency is included in the slightly vulnerable category (score 1.7-2.5) found in Nagari Kurai and Nagari Suliki influenced by parameters of dependence on agriculture, income level and regional basic activities (LQ) , while the level of vulnerability is not vulnerable (score <1.7) in Nagari Sungai Rimbang and Nagari Tanjuang Bungo which is influenced by parameters of dependence on agriculture and income levels.